Óleo volátil e antioxidantes de folhas de virola michelii heckel (myristicaceae) - Torres, Zelina Estevam dos Santos (2004)
This work describes the phytochemical study of Virola michelii Heckel that occur in the Amazon Region popularly known as ucuúba-preta and its leaves are used in the popular medicine as hot poultice on the skin, to treat infections caused by fungus. The fresh smashed leaves of Virola michelii submitted to the hydrodistilation afforded a volatile oil, which analyzed through coupled system gas chromatograph to mass spectrometer evidenced the occurrence of one monoterpene and of seventeen sesquiterpenes. The ethyl alcohol extract of V. michelii leaves was fractionated by ethyl acetate and aqueous methanol partition, followed by solvent evaporation of the fractions, yielded the respective residues. The ethyl acetate residue submitted to chromatographic techniques, allowed the isolation of three compounds, two furofuran lignan, “eudesmin” (rel- (1S,2R,5R,6S)-2,6-di-(3,4-dimethoxyphenyl]-3,7-dioxabicyclo[3.3.0]octane) and “phillygenol” rel-(1S,2S,5R,6R)-6-(4-hydroxy-3-methoxyphenyl)-2-(3,4-dimethoxyphenyl)-3,7- dioxabicyclo[3.3.0]octane and one phytosterol, the β-sitosterol. The structural determination was based on the interpretation of the 1 H and 13C nuclear magnetic resonance spectra and mass spectra. The isolated furofuran lignans were submitted to test for antioxidant activity with DPPH radical followed by photometric detection. It was observed that the phillygenol was more active than eudesmin, in the assay which quercetin was used as standard.